An Investigation on Identity Challenges Faced by Muslim Women Immigrants in Europe - Reyhanesadat Gerami; Younes Nourbakhsh; Rasoul Sadeghi (زن در توسعه و سیاست)
The emergence of various conflicts and challenges as a result of Muslims' presence in European countries as well as the growing Muslim diaspora within a predominately secular context have sparked significant concerns in the field of social sciences. Concurrently, it is imperative to address the process of self-identification among Muslim immigrant women in Europe, as well as the potential obstacles they encounter in relation to their religious identity. Numerous studies have been conducted on this topic. This investigation implements a qualitative meta-analysis methodology to evaluate research conducted between 2010 and 2023 regarding the religious identity challenges of Muslim women in the European diaspora. The host society's negative attitudes and behaviors, the imposition of specific lifestyles on Muslim women, the uneven progression of Muslim immigrant women, internal scrutiny and prejudice, the clash between Islamic and European lifestyles, and the experience of double marginalization were all identified as six religious identity challenges. Muslim women have adopted four fundamental strategies: personalizing their religious identity, engaging in membership and participation within Islamic centers, embracing multidimensional and flexible identities, and endorsing a discourse of pure Islam. Indeed, this study illustrates that Muslim immigrant women in European societies are subjected to mutual pressures from both the host and their own communities. They attempt to manage these pressures and achieve a sense of equilibrium in their daily lives by implementing a diverse array of strategies.